Síntese e caracterização de novas moléculas derivadas da mistura de ácidos graxos do óleo da mamona (Ricinus Communis l.) para aplicação em biolubrificantes - Rios, Ítalo Castro (2021)
The frequent rise in the oil price and the possibility of depletion reserves have been motivated the researchers to search for fuels and derivatives, like alternative lubricants based on different vegetable oils and/or animals. Thus, the present work aimed to: a comparative study between PTSA and Amberlyst-15 dry catalysts, produce 26 samples of biolubricants from mixture castor oil fatty acids, structurally modifying them through organic reactions, such as: esterification, epoxidation and oxirane rings opening, study the antioxidant additives TBHQ, XTREN 8 e 12, NAUGALUBE® and ascorbic acid, in different concentrations to evaluate their influence on oxidative stability values, study the biodegradability rate from the samples mineral oil, vegetable oil, mixture of fatty acids and biolubricants, using the bio-kinetics method and evaluate the biolubricant samples thermal degradation with different polarities. The study carried out between the catalysts showed that PTSA catalyst was the most efficient. Then, the alcohols methanol, ethanol, propanol, 3-methyl-1-butanol, butanol, tert-butanol, hexanol, cyclohexanol, octanol and 2-ethylhexanol were used in the esterification reaction to evaluate esters physicochemical properties structural influence, with this, the esters produced from the 3-methyl-1-butanol, 2-ethylhexanol and propanol alcohols were chos,n to continue the structural modification process of mixture castor oil fatty acid. Then, an epoxidation reaction was carried out, also measuring the physical-chemical properties. Then, the epoxidized esters were subjected to oxirane rings opening reactions with the reagents water, 3-Methyl-1-Butanol, Butanol, 2-Ethylhexanol, Iso-Butyric Acid and Butyric Acid, for the production of biolubricants with different polarities. The physical-chemical parameters were analyzed and it was possible to conclude that the obtained materials have a high potential for application as biolubricants, mainly for having excellent cold properties and for meeting the SAE and ISSO viscosity classifications. The antioxidant additives test and the blend additives test, primary and oxygen remover, in a biolubricant sample, allowed us to observe that the antioxidant concentration higher, the longer the oxidative stability time and that the antioxidants composition influences directly in this physical-chemical parameter. The biodegradability study, without microorganisms use, among the samples evaluated showed that the vegetable oil had the shortest half-life, 12 days, and the highest biodegradability rate 65%, unlike its mineral analog, which showed a half-life of 222 days and a low biodegradability rate. The thermal analysis study showed that different polarities of the biolubricants directly influence the activation energy values, in this case, the more polar biolubricant, which has a greater amount of hydroxyl in its structure, presented higher values than the apolar biolubricant. The results are encouraging for the synthesized materials industrial application, since the different reagents used in the materials synthesis serve a wide range in the industrial scenario use.